Targeting the Histamine H4 Receptor: Future Drugs for Inflammatory Diseases - Correa, Michelle F.; dos Santos Fernandes, Joao Paulo (Current Organic Chemistry, 2018)
Background: Histamine is a chemical transmitter widely distributed in the human body. It exerts its effects through the interaction with histaminergic receptors (H1R to H4R). The H4R is mainly expressed in hematopoietic cells, especially those involved in immune and inflammatory responses, and thus it is an important target for novel antiinflammatory agents for the treatment of disorders such as asthma, dermatitis, rheumatoid arthritis, peritonitis, inflammatory bowel disease and allergic rhinitis. Current pharmacological therapy for the treatment of such inflammatory disorders includes poorly effective drugs in many cases, also causing important adverse reactions. Accordingly, the development of new drugs has been widely explored, especially those with a different mechanism of action from NSAIDs and corticosteroids. Discussion: H4R antagonists/inverse agonists have demonstrated potential anti-inflammatory properties and thus several ligands have been reported, showing efficacy in several clinical and preclinical studies. The indolcarboxamides, aminopyrimidines, quinoxalines and quinazolines have been the most critically explored scaffolds to achieve highly selective and potent antagonists/inverse agonists. These derivatives have shown in vivo activity and important contributions for the structure-activity relationship data. Conclusion: In this paper, a review of the main ligands is undertaken and reported in the literature showing in vivo anti-inflammatory activity and potential therapeutic application.
Keywords: H4R antagonists